AIAA Atmospheric Flight Mechanics Conference 2010
DOI: 10.2514/6.2010-7950
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Spline-Based Global Nonlinear Aerodynamic Model for the Cessna Citation II

Abstract: A new method is proposed for the identification of global nonlinear models of aircraft non-dimensional force and moment coefficients. The method is based on a recent type of multivariate spline, the multivariate simplex spline, which can accurately approximate very large, scattered nonlinear datasets in any number of dimensions. The new identification method is used to identify a global nonlinear aerodynamic model of high dimensionality for the Cessna Citation II laboratory aircraft operated by the Delft Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The aim of this setup is to update an a-priory aerodynamic model online in case of a failure with adaptive simplex splines to eliminate model errors within the NDI control system. In [12] the F-16 aerodynamic model is identified with multivariate splines using flight testing based system identification techniques from [10,16,17]. This is an accurate global model and is used as the a-priori nominal onboard aerodynamic model in this study.…”
Section: Fault Tolerant Flight Control Methodsmentioning
confidence: 99%
“…The aim of this setup is to update an a-priory aerodynamic model online in case of a failure with adaptive simplex splines to eliminate model errors within the NDI control system. In [12] the F-16 aerodynamic model is identified with multivariate splines using flight testing based system identification techniques from [10,16,17]. This is an accurate global model and is used as the a-priori nominal onboard aerodynamic model in this study.…”
Section: Fault Tolerant Flight Control Methodsmentioning
confidence: 99%
“…In this section methods from [11,13,14] are used to identify the F-16 aerodynamic model using multivariate splines and ordinary polynomials. The data used to identify the aerodynamic models is generated with a high-fidelity wind tunnel dataset of the F-16.…”
Section: Identification Of the F-16 Aerodynamic Modelmentioning
confidence: 99%
“…Multivariate simplex splines have recently been used in a framework for aerodynamic model identification [12][13][14], where it was shown that they can more accurately approximate both local and global scale system nonlinearities than methods based on ordinary polynomials. The proven advantages of the simplex splines as powerful, numerically stable, and transparent nonlinear function approximators makes them well suited to replace current onboard models, thereby improving the performance and robustness of nonlinear model-based flight control systems.…”
Section: Introductionmentioning
confidence: 99%
“…This model was identified using flight data collected during 76 longitudinal 3211 flight test maneuvers. 21 Flight path reconstruction techniques based on an iterated extended Kalman filter (IEKF) were used to get a crisp estimation of aircraft state. 32 The linear regression scheme for multivariate simplex splines from Sec.…”
Section: Aerodynamic Model Validationmentioning
confidence: 99%